(3TQM bhGYO GdCMcGes - (3GHf GdeXaQ, eMeO Hf MSf Hf eMeO Hf YHO Gddg, J (B1375(3g`s ((3eMeO MSfs)
(3ChdgG (B:s
(3GdMeO ddg Ydi fYeGFg hHdGFg(B... (3cJGH GdRcGI hhLhHgG ef VQhQjGJ GdOjf(B...s
(3BNQgG (B:s
(3GdCbQH CLRGA GdUGY ef fhYjf Yf YHOg(B... (3hYf faSg hcd ef jYhdg (B... (3Je bSe GdRcGIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B6(3, U(B95s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis